Sevuparin for the treatment of acute pain crisis in patients with sickle cell disease: a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial. Issue 5 (May 2021) - Biemond, Bart J; Tombak, Anil; Kilinc, Yurdanur; Al-Khabori, Murtadha; Abboud, Miguel; Nafea, Mohammed; Inati, Adlette; Wali, Yasser; Kristensen, Jens; Kowalski, Jan; Donnelly, Ellen; Ohd, John; et al.
Summary: Background: There are no approved treatments for vaso-occlusive crises in sickle cell disease. Sevuparin is a novel non-anticoagulant low molecular weight heparinoid, with anti-adhesive properties. In this study, we tested whether sevuparin could shorten vaso-occlusive crisis duration in hospitalised patients with sickle cell disease. Methods: We did a multicentre, double-blinded, placebo-controlled, phase 2 study in 16 public access clinical hospitals in the Netherlands, Lebanon, Turkey, Bahrain, Oman, Saudi Arabia, and Jamaica. Patients aged 12–50 years with a diagnosis of sickle cell disease (types HbSS, HbSC, HbSβ 0 -thalassaemia, or HbSβ + -thalassaemia) on a stable dose of hydroxyurea, hospitalised with vaso-occlusive crisis for parenteral opioid analgesia with a projected stay of more than 48 h were included in the study. Patients were randomly assigned (1:1) using a computer-generated randomisation scheme to receive sevuparin (18 mg/kg per day) or placebo (NaCl, 0·9% solution) intravenously for 2–7 days until vaso-occlusive crisis resolution. All individuals involved in the trial were masked to treatment allocation. The analysis was done in the intention-to-treat population. The primary endpoint was time to vaso-occlusive crisis resolution defined as freedom from parenteral opioid use (in preceding 6–10 h); and readiness for discharge as judged by the patient or physician. The trial is registered with ClinicalTrials.gov, NCT02515838 . Findings: Between Oct 7, 2015, and Feb 10, 2019, 144 patients were randomly assigned and administered sevuparin (n=69) or placebo (n=75). The median age was 22·2 years (range 12·2–33·6), 104 (72%) 144 were adults (18 years or older), and 90 (63%) were male and 54 (37%) were female. The intention-to-treat analysis for the primary endpoint showed no significant difference in median time to vaso-occlusive crisis resolution between the sevuparin and placebo groups (100·4 h [95% CI 85·5–116·8]) vs 86·4 h [70·6–95·1]; hazard ratio 0·89 [0·6–1·3]; p=0·55). Serious adverse events occurred in 16 (22%) of 68 patients in the sevuparin group and in 21 (22%) of patients in the placebo group. The most frequent treatment-emergent adverse events were pyrexia (17 [25%] in the sevuparin group vs 17 [22%] in the placebo group), constipation (12 [18%] vs 17 [22%]), and decreased haemoglobin (18 [26%] vs 9 [12%]). There were no deaths in the sevuparin group and there was one (1%) death in the placebo group after a hyper-haemolytic episode due to alloimmunisation. Interpretation: This result, as well as the results seen in other clinical studies of inhibitors of adhesion in sickle cell disease, suggest that selectin-mediated adhesion might be important in the initiation, but not maintenance of vaso-occlusion, indicating that strategies to treat vaso-occlusive crises differ from strategies to prevent this complication. Funding: Modus Therapeutics.